Beyond Timbuktu : an intellectual history of Muslim West Africa - Kane, Ousmane (Cambridge, Massachusetts ; London, England : Harvard Universit y Press, 2016)
"By 2013, many people worldwide had heard about Timbuktu as a center of learning where thousands of Arabic manuscripts are preserved, some of which were destroyed by fanatics during the French counteroffensive to halt the expansion of Islamists in Mali. But few people know that Ti mbuktu was only one of many centers of Islamic learning in precolonial West Africa. This book analyses the rise and transformation of Arabo-Is lamic erudition in West Africa from the beginning of the spread of Isla m through the colonial period to the twenty-first century. It highlight s the contribution of Muslim scholars in the production and transmissio n of knowledge and in shaping state and society in West Africa. It argu es that no study of the history of education or knowledge production in West Africa will be complete unless it pays attention to this intellec tual tradition. The book further shows how European colonialism obstruc ts historiography so that we know so little about it. Finally, the book analyze the transformation of West African educational system, in the twentieth and twenty first century and shows that far from declining, t he Islamic tradition of West Africa has gained vitality in the postcolo nial period."--
Timbuktu studies: the geopolitics of the sources -- The growth and p olitical economy of scholarship in the Bilad al-Sudan -- The rise of cl erical lineages in the Sahara and the Bilad al-Sudan -- Curriculum and knowledge transmission -- Shaping an Islamic space of meaning: the disc ursive tradition -- Islamic education and the colonial encounter -- Mod ern Islamic institutions of higher learning -- Islam in the postcolonia l public sphere -- Arabophones triumphant: Timbuktu under Islamic rule.
Includes bibliographical references and index.
Keywords: Islamic learning and scholarship -- Africa, West -- History; Islamic learning and scholarship -- Mali -- Tombouctou -- History; Education -- Africa, West -- History; Education -- Political aspects -- Africa, West -- History; Africa, West -- Intellectual life; Africa, West -- Civilization -- Islamic influences